PEMBANGUNAN DAERAH DALAM KEMISKINAN DAN KONVERGENSI/ DIVERGENSI WILAYAH - Doddy Aditya Iskandar; Indra Andrianto (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2019)
A integrated and sustainable development is oriented towards improving people's welfare. However, disparity and poverty are still issues of development. Infrastructure and a sustainable inclusive economy are the priorities of national policies to reduce regional and socio-economic disparities by increasing connectivity between regions. The purpose of the study is to identify the conditions that are necessary and sufficient in regional development through government spending and infrastructure and economic programs on poverty as an indicator of regional disparity. This study uses a qualitative and quantitative